2012
DOI: 10.1007/s10875-012-9793-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Variability of Family Members with the C104R Mutation in Transmembrane Activator and Calcium Modulator and Cyclophilin Ligand Interactor (TACI)

Abstract: The C104R mutation does not correlate with the clinical phenotypes in this family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
0
42
0
1
Order By: Relevance
“…Mutations of these genes have been identified in healthy people, albeit at a lower frequency than symptomatic individuals [11,12]. We and others have shown that C104R mutations of the TACI gene do not segregate as expected with symptomatic family members [13]. Current thought is that these genes predispose to CVID rather than cause it.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Mutations of these genes have been identified in healthy people, albeit at a lower frequency than symptomatic individuals [11,12]. We and others have shown that C104R mutations of the TACI gene do not segregate as expected with symptomatic family members [13]. Current thought is that these genes predispose to CVID rather than cause it.…”
Section: Introductionmentioning
confidence: 74%
“…In clinical practice, patients with slightly reduced IgG levels would rarely be investigated, particularly if they are symptomatically well. Impaired vaccine response is the second and most contentious criterion [13]. The ESID/PAGID diagnostic criteria do not specify which vaccines should be used [13].…”
Section: Critical Analysis Of the Esid/pagid Criteria For Cvidmentioning
confidence: 99%
See 1 more Smart Citation
“…Other variants that impair signaling by TACI are also found, albeit at lower frequencies, in normal individuals (20). Still more curious, individuals homozygous for C104R exhibit a milder phenotype of CVID and are less likely to develop autoimmunity than are individuals heterozygous for C104R (14,18,21), and some respond normally to vaccination despite having hypogammaglobulinemia (22). The vast range of manifestations associated with TACI variants in human subjects, from normal to severe CVID, and the reciprocal impact of gene dosage on the severity of the disease suggest that either background genes exert more impact on phenotype than any TACI allele, or the high prevalence of TACI variants is adaptive in response to environmental factors, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Мутации этих генов были идентифицированы у здоровых людей [22,23,24]. Существует теория о том, что у «здоровых» людей могут обнаруживаться эти гены, однако, первые клинические признаки ОВИН начнут проявляться в старческом возрасте (плечо генов) [13].…”
Section: общий вариабельный иммунодефицит: клиника и диагностикаunclassified